Barriers of using Hospital Information System for Decision-Making: A Qualitative Study - Mohamed, Mussa Suliman; Setyonugroho, Winny; Pribadi, Firman (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Information technology applications play a major role in improving the services provided to patients in healthcare settings. Hospital Information System (HIS) is expected to facilitate information management and decision making, thus enhancing patient services. Purpose of this study is to explore the barriers that healthcare practitioners in PKU Muhammadiyah Bantul Hospital faces during using HIS for decision making. Method: This research is a qualitative study. Depth-interviews were carried out with six respondents (Two Clinicians, Three Managers, and One Director), interviews were recorded and transcribed for analysis, a list of codes has produced representing themes identified in the textual data. Results: Data in the HIS were not optimal due to the insufficiency of the system in generating the necessary information for decision-making. Raw data, not real time data, and incomplete data between units were the most barriers that decision makers faced. Conclusion: One of the crucial keys of a good performance of healthcare providers is hospital information system that ensures the production, analysis, and providing a reliable and timely information, making it easy for managers and doctors to make managerial and clinical decisions more effectively.